PENGARUH TINGKAT PENGANGGURAN TERHADAP TINGKAT INFLASI DI PROPINSI JAWA TIMUR TAHUN 2003-2011 - Imam Buchori; Lina Ambarwati Priono (El-Qist: Journal of Islamic Economics and Business (JIEB), 2014)
Research methods used in this research include: gathering together the data using the method of data collection the documentary, analyzed using simple regression analysis processed using SPSS 16 for Windows, using the inductive mindset. The unemployment rate that occurred in the province of East Java in 2003-2011 fluctuated between 3.00 and 6.00, as does the level of inflation that occurred in the province of East Java, demonstrated by Philips curve. After doing the analysis, obtained by the regression equation: Y = -2,218 + 1,490X. The correlation coefficient (R) obtained is 0,462. It can be concluded that both variables have a positive relationship. Based on the analysis of the results obtained, it can be drawn the conclusion that the influence that derived from the analysis results are positive, meaning that there is a weak influence between the unemployment rate and inflation rates in the province of East Java. Advice that can be given to the need to further research examined the relationship of other variables that their influences are strong against the inflation rate that occurs. And, for the future research, it could use the data with the greater amount.